2013
DOI: 10.1099/ijs.0.051839-0
|View full text |Cite
|
Sign up to set email alerts
|

Saccharothrix saharensis sp. nov., an actinomycete isolated from Algerian Saharan soil

Abstract: The taxonomic position of a novel actinomycete, strain SA152 T , isolated from a sample of Algerian Saharan soil, was determined using a polyphasic taxonomic approach. The strain produced abundant aerial mycelium and fragmented substrate mycelium on most media tested. Chemotaxonomically and phylogenetically, the strain was related to the members of the genus Saccharothrix. Results of 16S rRNA gene sequence comparison revealed that strain SA152 T shared the highest degree of 16S rRNA gene sequence similarity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Labeda et al (1984) proposed the genus Saccharothrix for actinomycetal strains that were characterized by fragmentation of both the substrate and aerial mycelia into rods and ovoid elements, a type III cell wall containing meso -diaminopimelic acid without glycine, galactose, rhamnose and small amounts of mannose as diagnostic whole cell sugars, a phospholipid type PII (phosphatidylethanolamine) or PIV (phosphatidylethanolamine and phospholipids containing glucosamine) pattern (Labeda & Lechevalier, 1989), and MK-9(H 4 ) as the predominant menaquinone, while mycolic acids were absent (Labeda & Kroppenstedt, 2000). The presence of members of the genus Saccharothrix has been reported previously in Saharan soils with several novel isolates, such as Saccharothrix algeriensis DSM 44581 T (Zitouni et al , 2004a), Saccharothrix hoggarensis DSM 45457 T (Boubetra et al , 2013a) and Saccharothrix saharensis DSM 45456 T (Boubetra et al , 2013b). Moreover, many of these Saharan strains were shown to produce new antibiotics such as mutactimycins (Zitouni et al , 2004b), dithiolopyrrolones (Bouras et al , 2008) and chloramphenicol (Aouiche et al , 2012).…”
supporting
confidence: 52%
“…Labeda et al (1984) proposed the genus Saccharothrix for actinomycetal strains that were characterized by fragmentation of both the substrate and aerial mycelia into rods and ovoid elements, a type III cell wall containing meso -diaminopimelic acid without glycine, galactose, rhamnose and small amounts of mannose as diagnostic whole cell sugars, a phospholipid type PII (phosphatidylethanolamine) or PIV (phosphatidylethanolamine and phospholipids containing glucosamine) pattern (Labeda & Lechevalier, 1989), and MK-9(H 4 ) as the predominant menaquinone, while mycolic acids were absent (Labeda & Kroppenstedt, 2000). The presence of members of the genus Saccharothrix has been reported previously in Saharan soils with several novel isolates, such as Saccharothrix algeriensis DSM 44581 T (Zitouni et al , 2004a), Saccharothrix hoggarensis DSM 45457 T (Boubetra et al , 2013a) and Saccharothrix saharensis DSM 45456 T (Boubetra et al , 2013b). Moreover, many of these Saharan strains were shown to produce new antibiotics such as mutactimycins (Zitouni et al , 2004b), dithiolopyrrolones (Bouras et al , 2008) and chloramphenicol (Aouiche et al , 2012).…”
supporting
confidence: 52%
“…Although Actinomadura species is known as an agent of desert areas [ 15 ], we isolated it from a patient, originally from a humid region (880 mm rainfall), which supports the findings reported by Zait et al [ 14 ]. Contrary to the little information found about the human actinomycetoma, the search for actinomycetes in the environment (water and soils) was performed in several parts of Algeria, in particular in the south and north-eastern regions, allowing to isolate several genera such as Actinomadura, Saccharothrix, and Streptomyces [ 16 19 ]. Imported cases of actinomycetoma have been already reported in European countries such as Italy [ 20 ], France [ 21 ] and Switzerland [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The arid soils of the Algerian Sahara have been shown to be rich in members of the Saccharothrix genus (Sabaou et al, 1998, Zitouni et al, 2005) including new species, such as Saccharothrix algeriensis NRRL B-24137 T (Zitouni et al, 2004a), Saccharothrix hoggarensis DSM 45457 T , Saccharothrix saharensis DSM 45456 T , Saccharothrix tamanrassetensis DSM 45947 T (Boubetra et al, 2013a, Boubetra et al, 2013b, Boubetra et al, 2015), Saccharothrix isguenensis DSM 46885 T and Saccharotrix ghardaiensis DSM 46886 T (Bouznada et al, 2016, Bouznada et al, 2017). In addition, many studies have shown the ability of Saccharothrix strains isolated from these soils to produce new or known antibiotics, such as dithiolopyrrolones (Lamari et al, 2002, Bouras et al, 2008, Merrouche et al, 2011), anthracyclines (Zitouni et al, 2004b) and chloramphenicol (Aouiche at al., 2012).…”
Section: Introductionmentioning
confidence: 99%